Effect of Economic Growth, Industrialization, and Urbanization on Energy Consumption in Nigeria: A Vector Error Correction Model Analysis - Ayinde, Adedoyin Ramat; Celik, Bilal; Gylych, Jelilov (International Journal of Energy Economics and Policy, 2019)
Poor energy production and consumption bedevils the state of Nigeria, for which distribution of energy is concentrated in the wealthy and urban middle class with the country's large poor population denied access. The current annual production is very low, and development of the sector is a challenge. Basically, additional infrastructure is needed to increase production which can feasibly be acquired through raising energy prices. However, a rise in price prohibits access to services for a large part of the population. Inability to raise energy production has a substantial impact on individuals and businesses alike. For businesses, frequent power outages bring inefficiency in the production of goods and services, resulting in stunted growth for local companies and discouraging international investors. For individuals, poor energy consumption impacts negatively on living standards. The accumulative effect of poor energy production and consumption over the years can greatly impact on the continent's economic growth and development. Present economic conditions may worsen with high population growth and rising urbanisation, hence, the need for a rapid and intensified strategy for energy development of the nation. Consequently, this study analyses the relationship between energy consumption on the one hand and economic growth, industry growth and urban growth for the nation. Using data for the period 1980-2016, a VEC model is analysed with the Granger causality test, impulse response function and variance decomposition. Using the Johansen cointegration test, one cointegrating relationship is found which led to conducting the VECM. It is found that a long run causal relationship exists only for GDP growth. That is, GDP only possess the correct sign and statistically significant level with the speed of adjustment back to equilibrium at 14 per cent. No short-run causal relationship is observed between energy consumption on the one hand and economic growth, industry growth and urban growth. Only FDI as a control variable has a bidirectional short-run causal relationship with energy consumption. Keywords: Energy Production, Economic Development, Industrialization, Urbanization, Energy Challenges JEL Classifications: L38, L51, L98 DOI: https://doi.org/10.32479/ijeep.8175